Hasil Pengujian Aplikasi Permainan Pada Anak Usia 7-11 Tahun Untuk Meningkatkan Konsentrasi - Dimas Wahyu Wibowo; Pramana Yoga Saputra; Eka Larasati Amalia (SMARTICS Journal, 2021)
Research on the results of testing game applications in children aged 7-11 years aims to determine how to improve concentration skills. By using a children's concentration-enhancing game application, data will be collected using the results of the points obtained from each child who plays the game. These points are used as statistical calculations. These statistics are used to determine the comparison of the level of concentration in each game that has been carried out as an independent evaluation for children